1969
DOI: 10.1128/jvi.3.1.33-37.1969
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of Lysostaphin-treated Cells of Staphylococcus aureus

Abstract: After treatment with 1 unit of lysostaphin per ml for 3 min, two strains of Staphylococcus aureus, 233 and PS 44A HJD, were transfected with phenol-extracted deoxyribonucleic acid (DNA) from the staphylococcal bacteriophages, 53 and 44A HJD, respectively. The number of transfected cells was low in both systems, approximately two in 107 enzyme-treated cells. There was a saturation effect at high concentrations of DNA; optimal results were obtained at concentrations between 10 to 25 ,ug/ml. Growth curves and flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1971
1971
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Nomura et al (11) performed transformation in hypertonic broth containing low levels of penicillin and streptomycin. Riggs and Rosenblum (16) reported transfection of two strains of S. aureus with phage deoxyribonucleic acid (DNA) in hypertonic medium only when the cell walls of the recipients had been partially disrupted with lysostaphin. A system for transfection of S. aureus with intact cell walls was recently developed, with 0.1 M CaCl2 in distilled water used as the incubation medium for uptake of phage DNA (18).…”
mentioning
confidence: 99%
“…Nomura et al (11) performed transformation in hypertonic broth containing low levels of penicillin and streptomycin. Riggs and Rosenblum (16) reported transfection of two strains of S. aureus with phage deoxyribonucleic acid (DNA) in hypertonic medium only when the cell walls of the recipients had been partially disrupted with lysostaphin. A system for transfection of S. aureus with intact cell walls was recently developed, with 0.1 M CaCl2 in distilled water used as the incubation medium for uptake of phage DNA (18).…”
mentioning
confidence: 99%
“…Calcium was added to a final concentration of 0.004 M. The mixtures of phages and bacteria were allowed to stand at 37 C for 10 min to allow adsorption of phages and were then further incubated with shaking at 37 C until lysis occurred. The lysates were purified from bacteria and cell debris by centrifugation at 16,300 x g for 15 min. The phages were pelleted at 107,000 x g for 2 hr.…”
mentioning
confidence: 99%
“…The basic obstacle in effecting transformation appears to be the obtaining of high-molecular-weight, biologically active deoxyribonucleic acid (DNA) which would be resistant to the action of staphylococcal deoxyribonuclease, thus permitting the DNA to effect transformation. Riggs and Rosenblum (11) reported that two strains of Staphylococcus aureus were transfected with DNA obtained from staphylococcal phages in hypertonic media.…”
mentioning
confidence: 99%